(untitled) (Research, Society and Development, 2020)
This article aims to describe and understand the importance of inclusive physical education (PE) classes for the training of students with Down Syndrome (DS). The case study uses participant observation, interview and bibliographic research. The subjects are students and interviewed a teacher, from a state school of regular education in Cuiabá-MT, with children from 9 to 10 years old from a 5th grade class, which has a total of 25 students. Observation School has students of different genres, social class, encompassing with and without disabilities, as its methodology focused on development through inclusion, regardless of the student’s limitation. It can be observed then that EDF classes use cooperation in inclusion, with the purpose of training intellectually and spiritually developed people, capable and free of prejudice, ready for life.